Virtual Classroom Fisika sebagai Media Efektif Belajar Fisika (Penerapan Teknologi Informasi) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Nature of physics which is abstraction, empirical, and mathematical generate difficulty learn, to overcoming it require to learn effectively. So that learning needed by effective of motivation and enthusiasm. Information Technology with progress can be exploited to increase student motivation and enthusiasm, this matter pass e-learning. E-Learning earn implementation, either through computer network (Web Course Model, Web Centric Course Model, and Web Enhanced Course Mode!), and also with Personal Computer (ComputerBased Training (CBT), Computer-Managed Learning, Integrated Learning System (ILS), Intelligent Tutoring System (ITS), Job Aids, Computer-Aided Assessment (CAA),Drill & Practice, Multimedia, Hypermedia, Resource-Based Learning, and Simulation. Virtual Classroom represent one of the implementation from e-learning able to be accessed to pass network and earn is also used by in Personal Computer. Virtual Classroom can streamline to learn physics. From tables of result learn student physics, Virtual Classroom can improve effectiveness learn student, that is improving mean assess physics from 32,4 becoming 75,90, improving absorption learn from 32% becoming 75,9%, and improve complete learn from 0% becoming 84,16%.